Bibliografía sobre comunidad. - Cruz Sánchez, Gerardo; Hernandez Rayas, Omar (Andamios)
The article presents a bibliography on community as an emerging phenomenon in contemporary societies, compiling various sources of studies in areas such as anthropology, sociology, and economics. The studies are organized into categories that relate community to other phenomena, such as feminism, migration, and digital communities, highlighting the complexity and interconnection of these topics. Additionally, it addresses the difficulty of defining community in a universal way, suggesting that each research may encompass multiple categories. The bibliography aims to provide a valuable resource for those researching community and its multiple dimensions in the current context.